DI-081 A cooperation project between the hospital pharmacist and general practitioners about drug interactions in clinical practice. (25th February 2017) - Vinciguerra, V; Fantozzi, R; Cena, C; Fruttero, R; Rolle, C
Abstract : Background: Drug–drug interactions (DDIs) frequently occur in therapies and may generate adverse drug reactions (ADRs). One of the main causes is polypharmacy, especially in the elderly. Although not all DDIs give rise to dangerous ADRs, the majority are preventable, and so careful review should be taken when new drugs are prescribed to vulnerable subjects. Purpose: The purposes of our work were: (1) evaluation of DDI in general practitioner (GP) prescriptions; (2) establishment of a cooperation project between pharmacists and GPs to improve the culture of DDI management and patient care. Material and methods: In 2013, pharmacists from the local health district launched a cooperation project involving 48 GPs. As a first step, GPs were asked to select a list of 9 drug associations for which monitoring of interactions in their prescriptions could be recommended. Pharmacists' interventions were (1) analysis of 2012–2014 GP prescriptions according to the list of 9 DDIs chosen by GPs; (2) evaluation of solutions for DDI management, using the Micromedex DDI checker database and literature analysis; (3) dissemination of DDI information to GPs through training meetings; and (4) assessment of the efficacy of these actions through a questionnaire submitted to GPs in 2013. Results: (1) Prescriptions analysis: even if the number of prescriptions with DDI increased from 2012 to 2014 (+12%), we observed a reduction in DDI number (−14% in 2012–2013, −9% in 2012–2014), of which some were statistically significant (calcium carbonate+pronton pumps inhibitors—50%, p<0.0041, amoxicillin+lansoprazole—42%, p<0.0088). (2) Questionnaire: 75% of GPs completed the questionnaire. Literature analysis was considered interesting by 94% of respondents; solutions were adopted by 89% of GPs. Clinical improvement after application of the solutions was observed in 34%. Conclusion: The multidisciplinary approach was effective in increasing GP awareness of DDI and in reducing DDI prescriptions. The importance of GP training was evident from the feedback from the questionnaires. Pharmacists' contribution allowed for evident improvement in pharmacotherapy quality and resulted in benefit to the patients. No conflict of interest